Pensamento suicida, depressão e religiosidade em uma população privada de liberdade - RANUZI, Cristina (2018)
People in deprivation of liberty represent a risk group for suicide, with higher incidence rates when compared to the general population. With regard to prevention, suicidal ideation is an important target because it is an initial stage that precedes the suicide. However, research on the subject is still scarce. Thus, the main objective of this research was to analyze the influence of sociodemographic variables, health, prison context, religiousness and depression on the presence or absence of suicidal thoughts. This is a cross-sectional, analytical study with a quantitative approach. The population consists of 228 persons deprived of their liberty, female and male, of a Penitentiary located in the Triângulo Mineiro. The dice were collected through interviews and the instrument was composed of a sociodemographic questionnaire, health, prison context and presence of suicidal thoughts, by the Durel scale, to survey the religiosity scores and by the DASS 21 scale for symptom collection of depression. The majority of participants in this study had high religiosity organizational (80.7%), nonorganizational (95.2%) and intrinsic (82%). As to the outcome of the evaluation of the symptoms of depression, the majority of the participants were classified as within normality (61.8%). The presence of suicidal thoughts after incarceration was reported by 21.1% of the participants and, in terms of correlation analysis, it was found that being female was 7.2 times more likely to present suicidal thoughts (rcp = 7.197), not having a partner increases by 3 times (rcp = 3,446), and for each point in the total depression scale score, the chances of presenting suicidal thoughts increased by 21% (rcp = 1,216). No statistically significant correlations were found with the religiosity scores, even though they were elevated. Considering suicide, one of the main causes of preventable death worldwide this study is relevant of the expansion of knowledge about such phenomena. Understanding the violence of death as a result of suicide, as well as correlated factors, can better portray the profile and reality of persons deprived of liberty, may contribute to the instrumentalisation of future intervention actions and the promotion of barriers to their occurrence. In addition, Brazil is home to the third largest prison population in the world and the adequate process of resocialization has a direct impact on the life of every community, and a greater commitment to them is necessary to provide real opportunities for reconstruction of life.